2020
DOI: 10.3390/math9010030
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nanofluid Slip Flow over an Exponentially Stretching/Shrinking Permeable Sheet with Heat Generation

Abstract: An investigation has been done on the hybrid nanofluid slip flow in the existence of heat generation over an exponentially stretching/shrinking permeable sheet. Hybridization of alumina and copper with water as the base fluid is considered. The mathematical model is simplified through the similarity transformation. A numerical solver named bvp4c in Matlab software is utilized to facilitate the problem-solving process and dual solutions are attained. The influences of several pertinent parameters on the main ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…x Nn (local Nusselt number) with those of Wahid et al [37] and have reported in tabular form. In pursuance, foremost the values of the magnetic parameter, aligned magnetic field angle, radiation parameter and Eckert number are respectively taken as 3, which disclose venerable agreement between the numerical results and executed numerical scheme.…”
Section: Validation Of Numerical Findings and Schemementioning
confidence: 67%
“…x Nn (local Nusselt number) with those of Wahid et al [37] and have reported in tabular form. In pursuance, foremost the values of the magnetic parameter, aligned magnetic field angle, radiation parameter and Eckert number are respectively taken as 3, which disclose venerable agreement between the numerical results and executed numerical scheme.…”
Section: Validation Of Numerical Findings and Schemementioning
confidence: 67%
“…The temperature at the surface is T w and ambient temperature is T 1 . In view of the above assumption, the leading equations are [47][48][49][50][51].…”
Section: Problem Formulationmentioning
confidence: 99%
“…Sundar et al [24] classified hybrid nanofluids as a motivation in preparing the fluid flow to obtain further increment of heat transfer rate with augmented thermal conductivity of the involving nanofluids. In recent years, the authors of [25][26][27][28][29] conducted several other studies on hybrid nanofluid. Khashi'ie et al [30] numerically studied the mixed convection of Cu-Al 2 O 3 /water in a non-Darcy porous medium with thermal dispersion.…”
Section: Introductionmentioning
confidence: 99%